TRAINING ON DIFFERENTIATED LEARNING STRATEGIES WITH MERRDEKA FLOW FOR CHEMISTRY TEACHERS IN PALU CITY - Afadil, Afadil; Rahmawati, Sitti; Nuryanti, Siti; Diah, Anang Wahid M.; Nurmayanti, Yuli (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The development of the implementation of the independent curriculum today requires learning with a new paradigm to be realized through differentiated learning strategies so that each student learns according to their needs, culture, and stage of development. MGMP Chemistry in Palu City realizes the importance of making various efforts so that the chemistry learning process runs both in terms of delivering learning materials and implementing practicum in the laboratory is a tangible manifestation of differentiated learning. The current problems are (1) teachers are still confused about interpreting differentiated learning strategies as part of a new paradigm of learning through student-centered learning practices, (2) teachers have not been able to apply the unity of the learning cycle starting from competency mapping, process planning, and implementation of learning assessments, (3) the ability of teachers to formulate learning designs and assessments according to the characteristics of participants' needs Education is still lacking, and (4) teachers still experience obstacles in the realization of the Pancasila Student Profile through learning. The training participants were 30 people who were teachers of chemistry subjects who were members of the Chemistry MGMP group of SMA Kota Palu. This Community Service activity aims to provide an understanding of the principles and application of differentiated learning which includes differentiation of content, processes, and products in chemistry subject matter at the high school level or the same level as the MERRDEKA flow. Activities that have been carried out in the form of workshops, training, and mentoring are carried out with a participatory model. The resulting output targets are scientific publications, differentiated learning guidebooks, and IPR.